Nitrogen-doped carbon-coated catalyst as well as preparation method and application thereof
By ion exchange of MET-Zn to form a nitrogen-doped carbon-coated catalyst M@NC, the problems of poor hydrogenation activity and low selectivity in the liquid phase hydrogenation reaction are solved, and a catalyst with high activity, high selectivity and easy recovery is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411790322.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing non-precious metal catalysts have problems of poor hydrogenation activity and low selectivity in liquid phase hydrogenation reactions, which is difficult to meet industrial production needs.
By ion exchange with MET-Zn as a precursor, and replacing the Zn2+ ion nodes as Fe, Co or Ni, a nitrogen-doped carbon-coated catalyst M@NC is formed to improve the specific surface area of the catalyst and the dispersion of metal nanoparticles.
The catalyst has high activity, high selectivity and easy recovery characteristics, and is suitable for the liquid hydrogenation reaction of orthochloronitrobenzene, improving product selectivity and catalyst stability.
Smart Images

Figure BDA0005175155700000011 
Figure BDA0005175155700000012 
Figure BDA0005175155700000041
Abstract
Description
Technical Field
[0001] The invention relates to a nitrogen-doped carbon-coated catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of my country's chemical industry, catalytic technology has become the core technology to promote the chemical industry. Due to the scarcity and high cost of precious metal catalysts, they cannot meet the needs of the future chemical industry in the field of catalysis. As a good substitute for precious metal catalysts, non-precious metal catalysts are widely used in catalytic degradation of organic pollutants, organic synthesis and other reactions due to their low cost and abundant resources. In particular, non-precious metal catalysts with Fe, Co and Ni as active components can be magnetically recovered in heterogeneous reactions, which can greatly reduce the recovery cost.
[0003] o-Chloroaniline (o-CAN) is an important chemical intermediate, a colorless to light yellow oily liquid, used in the manufacture of azo dyes, pharmaceutical intermediates, lithium batteries and other chemical production fields. Due to its excellent performance and wide application, it has high market demand and economic value. At present, the industry mostly uses iron powder reduction and liquid phase catalytic hydrogenation to synthesize o-chloroaniline, and the reaction is shown in Formula 1 and Formula 2:
[0004]
[0005] Formula 1: Reaction formula of iron powder reduction method
[0006]
[0007] Formula 2: Reaction formula of catalytic hydrogenation method
[0008] In the actual industrial production process, although the iron powder reduction production process is relatively mature, it will produce a large amount of iron mud and acidic wastewater, which seriously pollutes the environment and has been gradually eliminated. The catalytic hydrogenation method is currently a hot research process due to its advantages such as process cleanliness. However, for the liquid phase hydrogenation reaction of nitroaromatics containing halogen atoms (-Cl), dehalogenation is easy to occur during the process of nitro hydrogenation to generate amino groups, resulting in low selectivity of o-chloroaniline. At the same time, catalysts with non-precious metals as active components usually face problems such as poor hydrogenation activity and are difficult to meet industrial production needs. Therefore, the development of a highly selective, highly active and economical non-precious metal liquid phase hydrogenation catalyst has become an important research direction.
[0009] Metal-organic frameworks (MOFs) are crystalline porous materials with a periodic network structure formed by the self-assembly of inorganic metal centers and organic ligands. In recent years, nitrogen-doped carbon-coated metal nanoparticle catalysts derived from the carbonization of MOFs have attracted widespread attention in catalytic hydrogenation reactions. Among them, MET is a type of MOF with extremely high nitrogen content, composed of divalent metal cations and 1H-1,2,3-triazole. Because this high-nitrogen-content MOF can form a nitrogen-doped carbon-coated structure with a high specific surface area in situ during the carbonization process, and has abundant nitrogen-doped active sites and highly dispersed metal active components. Therefore, MET-Zn is considered to be a potential excellent precursor for the preparation of nitrogen-doped carbon-coated metal nanoparticle catalysts. If the highly dispersed Zn in MET-Zn is 2+ Ion node replaced with Fe 2+ 、Co 2+ or Ni 2+ ions, and then carbonized at high temperature in an inert gas atmosphere to obtain a nitrogen-doped carbon-coated metal nanoparticle catalyst with a large specific surface area, small metal active component particle size and high dispersion, which can be recovered magnetically. This catalyst has the characteristics of high activity, high selectivity and easy recovery. It is of great significance to use it in the liquid-phase catalytic hydrogenation of o-chloronitrobenzene to synthesize o-chloroaniline. Summary of the invention
[0010] One of the purposes of the present invention is to provide a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange and its preparation method and application. The catalyst uses MET-Zn for ion exchange to replace Zn 2+ After the ion node, the magnetic Fe, Co or Ni is used as the metal active component to realize the magnetic recovery of the catalyst, thereby reducing the recovery cost of the catalyst.
[0011] The second object of the present invention is to provide a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange.
[0012] The third object of the present invention is to provide the use of the magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange in the liquid phase hydrogenation reaction of o-chloronitrobenzene, wherein the catalyst has excellent catalytic activity, stability and selectivity.
[0013] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0014] In a first aspect, the present invention provides a method for preparing a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange, the preparation method being carried out according to the following steps:
[0015] Step 1: dissolving anhydrous zinc chloride in a mixed solvent of N,N-dimethylformamide, deionized water and anhydrous ethanol, and then dropping ammonia water to adjust the pH of the mixed solution to 9.5-11.5; adding 1H-1,2,3-triazole, stirring at room temperature for 8-14 hours, collecting the white precipitate by centrifugation, washing and drying to obtain a MET-Zn precursor;
[0016] Step 2: The MET-Zn precursor obtained in step 1 and Fe, Co or Ni metal nitrate are dissolved in dimethyl sulfoxide solvent respectively, and then the two solutions are mixed, the reaction tube is sealed under nitrogen protection, and ion exchange is performed at 30-70° C. for 18-24 hours. After the ion exchange is completed, the ion-exchanged M-MET (M=Fe, Co, Ni) precursor is obtained after washing and drying;
[0017] Step 3: The ion-exchanged M-MET precursor obtained in step 2 is placed in an inert gas atmosphere at 500-800°C for 1-3 hours for carbonization, with a heating rate of 1-10°C / min and an inert gas flow rate of 20-100 mL / min to obtain a nitrogen-doped carbon-coated catalyst M@NC (M = Fe, Co, Ni).
[0018] Preferably, in step 1, the molar ratio of anhydrous zinc chloride:1H-1,2,3-triazole is 1:3-4, most preferably 1:3.0-3.5.
[0019] Preferably, in step 1, the volume ratio of N,N-dimethylformamide:deionized water:anhydrous ethanol is 0.5-1.5:1-2:1, more preferably 1:1-2:1, and further preferably 1:1.5:1.
[0020] Preferably, in step 1, the pH of the mixed solution is adjusted to 11.
[0021] Preferably, in step 1, stirring is performed at room temperature for 12 h.
[0022] Preferably, in step 1, the washing reagents are N,N-dimethylformamide and methanol solvent in sequence.
[0023] Preferably, in step 1, the drying conditions are: drying in a vacuum oven at 50-80° C. for 12-36 hours, more preferably drying in a vacuum oven at 60° C. for 24 hours.
[0024] Preferably, in step 2, the mass ratio of MET-Zn precursor: dimethyl sulfoxide = 1:50-150, more preferably 1:100, the mass ratio of Fe, Co or Ni metal nitrate: dimethyl sulfoxide = 1:10-50, more preferably 1:20; the mass ratio of MET-Zn precursor and Fe, Co or Ni metal nitrate = 1:1-12, more preferably 1:5-7, and further preferably 1:6.
[0025] Preferably, in step 2, the ion exchange temperature is 50° C. and the exchange time is 20 h.
[0026] Preferably, in step 2, the drying is performed in a vacuum oven at 100-180° C. for 10-24 h, more preferably in a vacuum oven at 150° C. for 18 h.
[0027] Preferably, in step 2, the selected metal precursor is nickel nitrate hexahydrate.
[0028] Preferably, in step 2, the washing reagent is N,N-dimethylformamide, methanol and dichloromethane.
[0029] Preferably, in step three, the selected inert gas is N2, the carbonization temperature is 600°C, the carbonization time is 2h, the heating rate is 2°C / min, and the nitrogen flow rate is 30mL / min.
[0030] In a second aspect, the present invention provides a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange, prepared according to the preparation method described in the first aspect.
[0031] In a third aspect, the present invention provides the use of the magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange in the liquid-phase catalytic hydrogenation reaction of o-chloronitrobenzene.
[0032] The o-chloronitrobenzene reactant and o-chloroaniline product structural formula of the present invention are as follows:
[0033]
[0034] Preferably, the application is as follows: o-chloronitrobenzene, solvent and nitrogen-doped carbon-coated catalyst are added to a high-pressure reactor, nitrogen is introduced to remove air, and then hydrogen is introduced to stir the reaction to generate o-chloroaniline. After the reaction is completed, the catalyst is magnetically recovered and put into the next cycle.
[0035] Preferably, the solvent is methanol.
[0036] Preferably, the mass amount of the nitrogen-doped carbon-coated catalyst is 2-10% of the mass of o-chloronitrobenzene, and most preferably 5%.
[0037] Preferably, in the reaction solution composed of o-chloronitrobenzene and a solvent, the mass fraction of o-chloronitrobenzene is 10 to 40 wt %.
[0038] Preferably, the hydrogen pressure is maintained at 1.0-1.6 MPa, more preferably at 1.2 MPa, and the reaction temperature is controlled at 60-100°C, optimally at 80°C.
[0039] Preferably, the stirring rate is 500-1000 rpm.
[0040] Compared with the prior art, the invention has the following advantages:
[0041] (1) The present invention provides a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange. MET-Zn is used as a precursor in the preparation process. MET-Zn can be prepared by stirring at room temperature and pressure. Compared with other MOFs, the preparation process is simple and can be mass-produced.
[0042] (2) The magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange provided by the present invention adopts MET-Zn for ion exchange during the preparation process. The magnetically recoverable nitrogen-doped carbon-coated liquid-phase hydrogenation catalyst derived therefrom has a large specific surface area, a small particle size of metal nanoparticles and is highly dispersed, and can contact with more reaction substrates and hydrogen, thereby improving the catalyst activity.
[0043] (3) The magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange provided by the present invention has a large number of nitrogen atoms doped on the carbon layer, and the extra lone pair electrons of the nitrogen atoms are sp 2 The delocalized π system of the hybridized carbon layer provides electrons and improves its electronic structure, especially the doping of pyridine nitrogen, which significantly reduces the band gap, thereby promoting the adsorption of reaction substrates and improving catalytic activity and selectivity.
[0044] (4) The magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange provided by the present invention is used in the liquid phase hydrogenation of o-chloronitrobenzene to prepare o-chloroaniline as a probe reaction, with high product selectivity; the catalyst has good stability and can be reused multiple times; it is highly safe during use; and it has high industrial application value.
[0045] (5) The magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange provided by the present invention is applied to the liquid phase hydrogenation of o-chloronitrobenzene to prepare o-chloroaniline as a probe reaction. Since the catalyst contains nickel metal, it can be magnetically recovered by a magnet after the reaction, thereby reducing the catalyst recovery cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 : (a) is a diagram showing the dispersion effect of the Ni@NC catalyst prepared in Example 1 in methanol solvent; (b) is a diagram showing the magnetic attraction effect of the Ni / NC catalyst prepared in Example 1 in methanol solvent.
[0047] Figure 2 is the XRD spectrum of the Ni@NC catalyst prepared in Example 1.
[0048] Figure 3 : (a) is the SEM image of MET-Zn prepared in Comparative Example 2 without adding a pH adjuster; (b)-(c) are SEM images of MET-Zn prepared in Example 1 with adding a pH adjuster. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way.
[0050] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0051] Comparative Example 1: Preparation method of Ni-MET precursor
[0052] 1.00 g of anhydrous zinc chloride was dissolved in a mixed solvent of 10 mL of N, N-dimethylformamide, 15 mL of deionized water, and 10 mL of anhydrous ethanol, and the mixture was stirred vigorously to fully dissolve; a 28% mass fraction of ammonium hydroxide solution was added dropwise to the solvent to adjust the pH of the solvent to 11; 1.62 g of 1H-1,2,3-triazole was added, and the mixture was stirred at room temperature for 12 hours, and the white precipitate was collected by centrifugation, and washed with N, N-dimethylformamide and methanol solvents. The obtained solid product was placed in a vacuum oven and dried at 60° C. for 24 hours to obtain the precursor MET-Zn. 1.00 g of MET-Zn and 6.00 g of nickel nitrate hexahydrate were dissolved in 100 mL and 120 mL of dimethyl sulfoxide solvent, respectively. The two solutions were then mixed, the reaction tube was sealed under nitrogen protection, and ion exchange was performed at 50 ° C for 20 h. After the ion exchange, the precipitate was washed with N, N-dimethylformamide, methanol, and dichloromethane, and the precipitate was placed in a vacuum oven at 150 ° C for 18 h to obtain the Ni-MET precursor after ion exchange.
[0053] Example 1
[0054] 1.00 g of anhydrous zinc chloride was dissolved in a mixed solvent of 10 mL of N, N-dimethylformamide, 15 mL of deionized water, and 10 mL of anhydrous ethanol, and the mixture was stirred vigorously to fully dissolve; a 28% mass fraction of ammonium hydroxide solution was added dropwise to the solvent to adjust the pH of the solvent to 11; 1.62 g of 1H-1,2,3-triazole was added, and the mixture was stirred at room temperature for 12 hours, and the white precipitate was collected by centrifugation, and washed with N, N-dimethylformamide and methanol solvents. The obtained solid product was placed in a vacuum oven and dried at 60° C. for 24 hours to obtain the precursor MET-Zn. 1.00g MET-Zn and 6.00g nickel nitrate hexahydrate were dissolved in 100mL and 120mL of dimethyl sulfoxide solvent respectively, then the two solutions were mixed, the reaction tube was sealed under nitrogen protection, and ion exchange was carried out at 50°C for 20h. After the ion exchange, the precipitate was washed with N,N-dimethylformamide, methanol, and dichloromethane, and the precipitate was placed in a vacuum oven at 150°C for 18h to obtain the Ni-MET precursor after ion exchange. The Ni-MET precursor was placed in a nitrogen atmosphere at 600°C for 2h for carbonization, the heating rate was 2°C / min, the nitrogen flow rate was 30mL / min, and the Ni@NC catalyst was obtained after cooling.
[0055] The dispersion effect diagram of the Ni@NC catalyst prepared in Example 1 in methanol solvent and the magnetic attraction effect diagram are shown in FIG. Figure 1 As shown in the figure, the solvent was restored to clarity after magnetic attraction, indicating that the catalyst has excellent magnetic recovery performance. Figure 2 As shown, the characteristic diffraction peaks of the (111), (200) and (220) crystal planes of Ni metal are weak, indicating that the Ni metal nanoparticles are small in size and highly dispersed.
[0056] Comparative Example 2: No pH adjuster added
[0057] 1.00g of anhydrous zinc chloride was dissolved in a mixed solvent of 10mL of N,N-dimethylformamide, 15mL of deionized water, and 10mL of anhydrous ethanol, and stirred vigorously to fully dissolve; 1.62g of 1H-1,2,3-triazole was added, and stirred at room temperature for 12h, and the white precipitate was collected by centrifugation, washed with N,N-dimethylformamide and methanol solvents, and the obtained solid product was placed in a vacuum oven at 60°C and dried for 24h to obtain the precursor MET-Zn. 1.00g of MET-Zn and 6.00g of nickel nitrate hexahydrate were dissolved in 100mL and 120mL of dimethyl sulfoxide solvents respectively, and then the above two solutions were mixed, and the reaction tube was sealed under nitrogen protection, and heated at 50°C for 20h for ion exchange. After the ion exchange, the precipitate was washed with N,N-dimethylformamide, methanol, and dichloromethane, and the precipitate was placed in a vacuum oven at 150°C and dried for 18h to obtain the Ni-MET precursor after ion exchange. The Ni-MET precursor was placed in a nitrogen atmosphere at 600°C for 2 hours for carbonization, with a heating rate of 2°C / min and a nitrogen flow rate of 30 mL / min. After cooling, the Ni@NC-2 catalyst was obtained.
[0058] The SEM images of MET-Zn prepared in Example 1 and MET-Zn prepared in Comparative Example 2 are as follows: Figure 3 As shown in the figure, the MET-Zn particles prepared without adding pH regulator are severely agglomerated, and the MET-Zn particles after pH adjustment present a typical octahedral configuration. It can be seen that adjusting the pH of the solvent will have a significant impact on the morphology and structure of MET-Zn, thereby affecting the catalytic performance of the catalyst.
[0059] Comparative Example 3: Ion exchange at room temperature
[0060] 1.00g of anhydrous zinc chloride was dissolved in a mixed solvent of 10mL of N,N-dimethylformamide, 15mL of deionized water, and 10mL of anhydrous ethanol, and stirred vigorously to fully dissolve; 1.62g of 1H-1,2,3-triazole was added, and stirred at room temperature for 12h, and the white precipitate was collected by centrifugation, washed with N,N-dimethylformamide and methanol solvents, and the obtained solid product was placed in a vacuum oven at 60°C and dried for 24h to obtain the precursor MET-Zn. 1.00g of MET-Zn and 6.00g of nickel nitrate hexahydrate were dissolved in 100mL and 120mL of dimethyl sulfoxide solvents respectively, and then the above two solutions were mixed, and the reaction tube was sealed under nitrogen protection, and the reaction was carried out at room temperature for 20h for ion exchange. After the ion exchange, the precipitate was washed with N,N-dimethylformamide, methanol, and dichloromethane, and the precipitate was placed in a vacuum oven at 150°C and dried for 18h to obtain the Ni-MET precursor after ion exchange. The Ni-MET precursor was placed in a nitrogen atmosphere at 600°C for 2 hours for carbonization, with a heating rate of 2°C / min and a nitrogen flow rate of 30 mL / min. After cooling, the Ni@NC-3 catalyst was obtained.
[0061] Comparative Example 4: No ion exchange
[0062] 1.00g of anhydrous zinc chloride was dissolved in a mixed solvent of 10mL of N,N-dimethylformamide, 15mL of deionized water, and 10mL of anhydrous ethanol, and stirred vigorously to fully dissolve; 1.62g of 1H-1,2,3-triazole was added, and stirred at room temperature for 12h, and the white precipitate was collected by centrifugation, washed with N,N-dimethylformamide and methanol solvent, and the obtained solid product was placed in a vacuum oven at 60°C and dried for 24h to obtain the precursor MET-Zn. MET-Zn was placed in a nitrogen atmosphere at 600°C for 2h for carbonization, with a heating rate of 2°C / min and a nitrogen flow rate of 30mL / min, and the Zn@NC-4 catalyst was obtained after cooling.
[0063] Comparative Example 5: No carbonization treatment
[0064] 1.00 g of anhydrous zinc chloride was dissolved in a mixed solvent of 10 mL of N, N-dimethylformamide, 15 mL of deionized water, and 10 mL of anhydrous ethanol, and it was stirred vigorously to be fully dissolved; 1.62 g of 1H-1,2,3-triazole was added, and after stirring at room temperature for 12 hours, the white precipitate was collected by centrifugation, and washed with N, N-dimethylformamide and methanol solvents. The obtained solid product was placed in a vacuum oven at 60°C and dried for 24 hours to obtain the precursor MET-Zn. 1.00 g of MET-Zn and 6.00 g of nickel nitrate hexahydrate were dissolved in 100 mL and 120 mL of dimethyl sulfoxide solvents, respectively. The two solutions were then mixed, and the reaction tube was sealed under nitrogen protection. The reaction was carried out at room temperature for 20 h for ion exchange. After the ion exchange, the precipitate was washed with N,N-dimethylformamide, methanol, and dichloromethane. The precipitate was placed in a vacuum oven at 150 ° C and dried for 18 h to obtain a Ni-MET precursor after ion exchange, which was recorded as Ni-MET catalyst.
[0065] Application Example 1
[0066] In a 250mL high-pressure reactor, 0.5g of the magnetically recoverable nitrogen-doped carbon-coated liquid-phase hydrogenation catalyst derived from MET-Zn ion exchange prepared in Example 1, 10g of o-chloronitrobenzene, and 80mL of methanol were added in sequence, and the reactor was sealed. The air in the reactor was replaced with nitrogen for 3 times, and then the nitrogen in the reactor was repeatedly replaced with hydrogen for 3 times, and the hydrogen pressure in the reactor was adjusted to 1.2MPa. After heating to 80°C, stirring (stirring rate 750rpm) was started and the reaction was carried out for 3h. After the reaction was completed, the catalyst was recovered by magnetic attraction with a magnet, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography. The separated solvent was washed with deionized water and methanol, and dried to obtain the target product.
[0067] Application Example 2
[0068] In a 250mL high-pressure reactor, 0.5g of the Ni@NC-2 catalyst prepared in Comparative Example 2, 10g of o-chloronitrobenzene, and 80mL of methanol were added in sequence, and the reactor was sealed. The air in the reactor was replaced with nitrogen three times, and then the nitrogen in the reactor was repeatedly replaced with hydrogen three times, and the hydrogen pressure in the reactor was adjusted to 1.2MPa. After heating to 80°C, stirring (stirring rate 750rpm) was started and the reaction was carried out for 3h. After the reaction was completed, the catalyst was recovered by magnetic attraction with a magnet, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the separated solvent was washed with deionized water and methanol, and dried to obtain the target product.
[0069] Application Example 3
[0070] In a 250mL high-pressure reactor, 0.5g of Ni@NC-3 prepared in Comparative Example 3, 10g of o-chloronitrobenzene, and 80mL of methanol were added in sequence, and the reactor was sealed. The air in the reactor was replaced with nitrogen three times, and then the nitrogen in the reactor was repeatedly replaced with hydrogen three times, and the hydrogen pressure in the reactor was adjusted to 1.2MPa. After heating to 80°C, stirring was started (stirring rate 750rpm), and the reaction was carried out for 3h. After the reaction was completed, the catalyst was recovered by magnetic attraction with a magnet, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the separated solvent was washed with deionized water and methanol, and dried to obtain the target product.
[0071] Application Example 4
[0072] In a 250mL high-pressure reactor, 0.5g of Zn@NC-4 prepared in Comparative Example 4, 10g of o-chloronitrobenzene, and 80mL of methanol were added in sequence, and the reactor was sealed. The air in the reactor was replaced with nitrogen three times, and then the nitrogen in the reactor was repeatedly replaced with hydrogen three times, and the hydrogen pressure in the reactor was adjusted to 1.2MPa. After heating to 80°C, stirring (stirring rate 750rpm) was started and the reaction was carried out for 3h. After the reaction was completed, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the separated solvent was washed with deionized water and methanol, and dried to obtain the target product.
[0073] Application Example 5
[0074] In a 250mL high-pressure reactor, 0.5g of Ni-MET prepared in Comparative Example 5, 10g of o-chloronitrobenzene, and 80mL of methanol were added in sequence, and the reactor was sealed. The air in the reactor was replaced with nitrogen for 3 times, and then the nitrogen in the reactor was repeatedly replaced with hydrogen for 3 times, and the hydrogen pressure in the reactor was adjusted to 1.2MPa. After heating to 80°C, stirring (stirring rate 750rpm) was started and the reaction was carried out for 3h. After the reaction was completed, the catalyst was filtered, the organic layer was separated, and the composition of the hydrogenation product in the filtrate was analyzed by high-performance gas chromatography; the separated solvent was washed with deionized water and methanol, and dried to obtain the target product.
[0075] Table 1 Comparison of catalyst performance in Examples 1 to 5
[0076] Application Examples catalyst Reaction time (mins) o-Chloronitrobenzene conversion rate (%) Product selectivity (%) 1 Ni@NC of Example 1 360 100.00 >99 2 Ni@NC-2 of Comparative Example 2 360 90.00 >89 3 Ni@NC-3 of Comparative Example 3 360 5.21 5.14 4 Zn@NC-4 of Comparative Example 4 360 0 0 5 Ni-MET of Comparative Example 5 360 0 0
[0077] The comparison between Example 1 and Comparative Example 2 shows that the addition of ammonium hydroxide to adjust the pH of the solvent during the preparation of the MET-Zn precursor will affect the morphology and structure of MET-Zn. The regular MET-Zn structure can obtain a larger specific surface area and is conducive to subsequent ion exchange. Therefore, the structure of MET-Zn will affect the catalytic performance and stability of its carbonization-derived catalyst. The comparison between Example 1 and Comparative Example 3 shows that the catalyst activity is significantly reduced when ion exchange is performed at room temperature, indicating that ion exchange requires a certain reaction temperature, otherwise the Zn in MET-Zn will not be 2+ Ion nodes cannot be completely replaced with Ni 2+ ions, resulting in a low content of Ni metal nanoparticles in the nitrogen-doped carbon-coated catalyst derived after carbonization, thereby showing poor catalytic activity. The comparison between Example 1 and Comparative Examples 4 and 5 shows that the catalytic activity of Zn metal as a hydrogenation active component is very weak, and the MOF precursor cannot be directly used as a hydrogenation catalyst. Its catalytic activity often comes from the electron transfer between the metal active component after carbonization of the MOF precursor and the graphene carbon layer with conductive properties.
[0078] Application Example 6
[0079] The experimental conditions were the same as those in Application Example 1, and the catalyst obtained by magnetic separation was repeatedly used in the next reaction. The composition of the hydrogenation product in the filtrate obtained in each application experiment was analyzed by high performance gas chromatography, and the results are shown in Table 2:
[0080] Table 2 Catalyst Example 1 Application Results
[0081]
[0082]
[0083] *The reaction conditions are the same as those in Application Example 1.
[0084] Application Example 7
[0085] The experimental conditions were the same as those in Application Example 2, and the catalyst obtained by filtration was repeatedly used in the next reaction. The composition of the hydrogenation product in the filtrate obtained in each application experiment was analyzed by high performance gas chromatography, and the results are shown in Table 3:
[0086] Number of applications Catalyst addition amount (g) Reaction time (mins) o-Chloronitrobenzene conversion rate (%) o-Chloroaniline yield (%) 1 0.5 360 91.00 90.15 2 0.5 360 84.10 79.45 3 0.5 360 64.29 60.57
[0087] *The reaction conditions are the same as those in Application Example 2.
[0088] Application Example 8
[0089] The experimental conditions were the same as those in Application Example 3, and the catalyst obtained by filtration was repeatedly used in the next reaction. The composition of the hydrogenation product in the filtrate obtained in each application experiment was analyzed by high performance gas chromatography, and the results are shown in Table 4:
[0090] Number of applications Catalyst addition amount (g) Reaction time (mins) o-Chloronitrobenzene conversion rate (%) o-Chloroaniline yield (%) 1 0.5 360 5.21 5.14 2 0.5 360 4.20 4.12 3 0.5 360 2.49 2.32
[0091] *The reaction conditions are the same as those in Application Example 3.
Claims
1. A method for preparing a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange, characterized in that: The preparation method is carried out according to the following steps: Step 1: dissolving anhydrous zinc chloride in a mixed solvent of N,N-dimethylformamide, deionized water and anhydrous ethanol, and then dropping ammonia water to adjust the pH of the mixed solution to 9.5-11.5; adding 1H-1,2,3-triazole, stirring at room temperature for 8-14 hours, collecting the white precipitate by centrifugation, washing and drying to obtain a MET-Zn precursor; Step 2: The MET-Zn precursor obtained in step 1 and Fe, Co or Ni metal nitrate are dissolved in dimethyl sulfoxide solvent respectively, and then the two solutions are mixed, the reaction tube is sealed under nitrogen protection, and ion exchange is performed at 30-70° C. for 18-24 hours. After the ion exchange is completed, the M-MET precursor after ion exchange is obtained after washing and drying; Step 3: The M-MET precursor obtained in step 2 after ion exchange is placed in an inert gas atmosphere and maintained at 500-800°C for 1-3 hours for carbonization, with a heating rate of 1-10°C / min and an inert gas flow rate of 20-100 mL / min to obtain a magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange.
2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of anhydrous zinc chloride:1H-1,2,3-triazole is 1:3-4, and most preferably 1:3.0-3.
5.
3. The preparation method according to claim 1, characterized in that: In step 1, the volume ratio of N,N-dimethylformamide:deionized water:anhydrous ethanol is 0.5-1.5:1-2:1, preferably 1:1-2:1, and more preferably 1:1.5:
1.
4. The preparation method according to claim 1, characterized in that: In step 1, the pH of the mixed solution is adjusted to 11.
5. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of MET-Zn precursor: dimethyl sulfoxide is 1:50-150, the mass ratio of Fe, Co or Ni metal nitrate: dimethyl sulfoxide is 1:10-50; the mass ratio of MET-Zn precursor and Fe, Co or Ni metal nitrate is 1:1-12.
6. The preparation method according to claim 1, characterized in that: In step 2, the ion exchange temperature is 50° C. and the exchange time is 20 h.
7. The preparation method according to claim 1, characterized in that: In step 2, the selected metal precursor is nickel nitrate hexahydrate.
8. The preparation method according to claim 1, characterized in that: In step three, the selected inert gas is N2, the carbonization temperature is 600°C, the carbonization time is 2h, the heating rate is 2°C / min, and the nitrogen flow rate is 30mL / min.
9. A magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange, prepared according to the preparation method of any one of claims 1 to 8.
10. Use of the magnetically recoverable nitrogen-doped carbon-coated catalyst derived from MET-Zn ion exchange as claimed in claim 9 in liquid-phase catalytic hydrogenation of o-chloronitrobenzene.
Citation Information
Patent Citations
Preparation of nitrogen doped carbon-encapsulated core-shell structure ferro-nickel nano-catalyst and application thereof in catalyzing o-chloronitrobenzene hydrogenation reaction
CN106732733A
Nitrogen-modified carbon-coated nickel catalyst as well as preparation method and application thereof
CN116020511A
Preparation method and application of structure-controllable graphene shell encapsulated nickel nanoparticle catalyst
CN116116417A
Preparation method of nitrogen-rich porous carbon coated iron nanoparticles for oxygen reduction reaction
CN116454295A
Nitrogen-doped carbon-coated catalyst, preparation method thereof and method for preparing m-xylylenediamine from m-phthalonitrile
CN117205923A
Cited By
Carbon layer coated modified catalyst as well as preparation method and application thereof
CN120714636A